ATTRACTING INVESTMENT AND ENHANCED IMPACT WHILE BUILDING INNOVATION POTENTIAL IN EDUCATION - Sabohat Gaziyevna Alimova; Narziev Zhaloliddin Paigamovich; Gulzoda Bekhzod Kizi Melieva (Western European Studies, 2025)
This article examines the issues of attracting investment into educational institutions, including secondary, vocational, and higher education. The article proposes a solution for creating an effective system for attracting private funds for the needs of educational institutions.
Keywords: education; investment; distance learning